La función ideológica del emprendimiento en la producción y reproducción de la vida en una zona rural de Colombia en el contexto del Posacuerdo de Paz - Oviedo, Carlos Fernando Torres (2020)
This thesis analyzes the ideological function of entrepreneurship in the production and reproduction of life in a rural area in the context of Peace Post-Agreement in Colombia. The Peace Agreement signed between the Colombian Government and the guerrilla of the Revolutionary Armed Forces of Colombia - People's Army (FARC-EP), in November 2016, put an end to a fifty year-old armed conflict for political power. One of the negotiated points was referred to rural poverty. A strategy to solve this problem was defined, among other commitments, under the understanding of being one of the historical conditions that caused the conflict. This strategy involves, within the programmed actions, to encourage and support “productive projects” of rural communities and guerrilla combatants. After three years of validity, it is possible to state that the Final Agreement has only been partially fulfilled and that the acts of violence persist, especially against social leaders who defend their territories from both legal and illegal economic projects. In this context, rural communities have been organizing themselves to guarantee the conditions of their existence. To carry out this analysis, the characteristics of the context of the Peace Agreement were described, aspects of the production and reproduction of the life of a rural community immersed were identified, the concept of ideology was reviewed, the main conceptual features of entrepreneurship were examined and some elements for an ontological critique of entrepreneurship as an ideology were proposed. This work allowed us to postulate that in this context the ideological function of entrepreneurship operates as an instrument through which the ruling classes aim to guide the production and reproduction of the life of rural communities towards the realization of economic activities aimed at the market. Simultaneously, the same ideological function of entrepreneurship tends to influence the practices of other economic actors linked to activities equally aimed at the market, which threaten the life of the rural communities. These two tendencies constitute complementary actions of the same expanding movement of production practices aimed at the market.